1999
DOI: 10.1016/s0954-6111(99)90094-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma brain natriuretic peptide levels in chronic respiratory failure with cor pulmonale

Abstract: Elevated plasma brain natriuretic peptide (BNP) levels have been described in patients with congestive heart failure and acute myocardial infarction. We measured plasma BNP levels in patients with chronic respiratory failure to evaluate the correlation between plasma BNP levels and pulmonary haemodynamics. Plasma BNP levels were measured in 28 patients with chronic respiratory failure accompanied by three underlying diseases [14 with chronic obstructive pulmonary disease (COPD), seven with sequelae of pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
3
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 24 publications
2
61
3
3
Order By: Relevance
“…NT-proBNP and BNP were influenced by age and renal dysfunction in accordance with other studies. [16][17][18][19] In contrast with other studies, they were not influenced by gender nor by the use of renin-angiotensin system blockers. [20][21][22] A limitation of the study is the small population of 103 nursing home residents, in one centre, which could lead to a selection bias in arriving at the prevalence of CHF of 23%.…”
Section: Discussioncontrasting
confidence: 64%
“…NT-proBNP and BNP were influenced by age and renal dysfunction in accordance with other studies. [16][17][18][19] In contrast with other studies, they were not influenced by gender nor by the use of renin-angiotensin system blockers. [20][21][22] A limitation of the study is the small population of 103 nursing home residents, in one centre, which could lead to a selection bias in arriving at the prevalence of CHF of 23%.…”
Section: Discussioncontrasting
confidence: 64%
“…Such elevations are usually smaller than those appreciated in left ventricular heart failure and negligible or absent in uncomplicated COPD exacerbation (Bando et al 1999).…”
Section: B-type Natriuretic Peptidementioning
confidence: 82%
“…In the present study we determined significant negative correlations between serum NT-proBNP with FEV 1 , FVC, IC and VC as well. Chi et al (25) determined positive correlation between PAP with NT-proBNP in COPD patients and Bando et al (27) found higher serum BNP levels in COPD patients with PH than COPD patients without PH. Leuchte et al (23) showed significant correlation between serum BNP levels with PAP in COPD patients with PAP>35 mm Hg at right heart catheterization.…”
Section: Discussionmentioning
confidence: 99%